2019
DOI: 10.1016/j.bpj.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Bacterial Outer Membrane Models: Neutron Reflectometry & Molecular Simulation

Abstract: The outer membrane (OM) of Gram-negative bacteria is an asymmetric bilayer having phospholipids in the inner leaflet and lipopolysaccharides in the outer leaflet. This unique asymmetry and the complex carbohydrates in lipopolysaccharides make it a daunting task to study the asymmetrical OM structure and dynamics, its interactions with OM proteins, and its roles in translocation of substrates, including antibiotics. In this study, we combine neutron reflectometry and molecular simulation to explore the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
3
39
0
1
Order By: Relevance
“…However, the exact thermotropic response of LPS in the outer leaflet may vary, depending on the composition (particularly the presence of hydrogen bond donors and acceptors) and size of the polysaccharide region of the LPS molecules incorporated ( 78 , 229 , 231 , 232 ). In vitro models of the OM using an asymmetric bilayer deposited on silicon or lipid-coated gold surfaces showed that the membrane has unusual mixed characteristics with elements of both liquid- and gel-phase lipids ( 233 , 234 ). The OM in these studies comprised “rough” LPS (containing the conserved polysaccharide core but lacking the O-antigen) ( Fig.…”
Section: More Than a MIX Of Lipid Typesmentioning
confidence: 99%
“…However, the exact thermotropic response of LPS in the outer leaflet may vary, depending on the composition (particularly the presence of hydrogen bond donors and acceptors) and size of the polysaccharide region of the LPS molecules incorporated ( 78 , 229 , 231 , 232 ). In vitro models of the OM using an asymmetric bilayer deposited on silicon or lipid-coated gold surfaces showed that the membrane has unusual mixed characteristics with elements of both liquid- and gel-phase lipids ( 233 , 234 ). The OM in these studies comprised “rough” LPS (containing the conserved polysaccharide core but lacking the O-antigen) ( Fig.…”
Section: More Than a MIX Of Lipid Typesmentioning
confidence: 99%
“…The outer membrane is another important structural element that in combination with peptidoglycan resist turgor pressure fluctuations [38] , [39] . The outer membrane has asymmetrical composition with an inner leaflet rich in phospholipids and an outer leaflet predominantly composed of polyanionic lipopolysaccharides (LPS) [40] , [41] . The polyanionic nature of LPS with numerous phosphate and acid sugar groups is stabilised by divalent cations (Mg 2+ and Ca 2+ ).…”
Section: Introductionmentioning
confidence: 99%
“…We have used NR to investigate this in detail. Previous studies have shown that an asymmetric d-DPPC (inner leaflet): Ra-LPS (outer leaflet) bilayer has been well established to mimic the wild-type Gram-negative bacterial OM (Figure A). Deuterated DPPC (d-DPPC) has been chosen to offer enough isotopic contrast between inner and outer leaflets under neutron measurements and provide a stable platform for the Ra-LPS outer leaflet to be deposited onto. Therefore we have investigated the interactions of cubosomes (32 μg/mL) with the d-DPPC: Ra-LPS OM, Ab 5075D OM and Ab 19609R OM using NR, whereby d-DPPC: Ra-LPS OM was devoted to representing those LPS-rich Gram-negative bacteria, i.e., A.…”
Section: Resultsmentioning
confidence: 99%